2008
DOI: 10.1074/jbc.m803813200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the JAK2 Inhibitor, AZ960, on Pim/BAD/BCL-xL Survival Signaling in the Human JAK2 V617F Cell Line SET-2

Abstract: The Janus-associated kinase 2 (JAK2) V617F mutation is believed to play a critical role in the pathogenesis of polycythemia vera, essential thrombocythemia, and idiopathic myelofibrosis. We have characterized a novel small molecule JAK2 inhibitor, AZ960, and used it as a tool to investigate the consequences of JAK2 V617F inhibition in the SET-2 cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 44 publications
(81 reference statements)
8
90
0
1
Order By: Relevance
“…Interestingly, pSTAT1 has been observed in a subpopulation of cells in extramedullary hematopoietic tissue from a JAK2 V617F -positive PV patient, and the activation of STAT1 has recently been shown to promote an ET versus a PV phenotype, which indicates the potential of STAT1 as an additional modifying factor of MPN disease progression. 41,42 These findings further highlight an interconnection between STAT1 and JAK2 V617F -STAT3/5 signal transduction, and support the concept that these proteins should be examined in concert to guide the use of JAK2 inhibitors like BMS-911543 in MPN and other malignancies. AVP, TMM, HW, DY, BP, XH, RV, YZ, SUR, GLT, LL, MMG, PRM, HS, JH, SLE, YB, EF, TLT KWM, EM, CM, FYL, AW and MVL are employees of Bristol-Myers Squibb, which generated BMS-911543 for clinical trials.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, pSTAT1 has been observed in a subpopulation of cells in extramedullary hematopoietic tissue from a JAK2 V617F -positive PV patient, and the activation of STAT1 has recently been shown to promote an ET versus a PV phenotype, which indicates the potential of STAT1 as an additional modifying factor of MPN disease progression. 41,42 These findings further highlight an interconnection between STAT1 and JAK2 V617F -STAT3/5 signal transduction, and support the concept that these proteins should be examined in concert to guide the use of JAK2 inhibitors like BMS-911543 in MPN and other malignancies. AVP, TMM, HW, DY, BP, XH, RV, YZ, SUR, GLT, LL, MMG, PRM, HS, JH, SLE, YB, EF, TLT KWM, EM, CM, FYL, AW and MVL are employees of Bristol-Myers Squibb, which generated BMS-911543 for clinical trials.…”
Section: Discussionmentioning
confidence: 59%
“…A unifying feature of this transcriptional profile was a core set of regulated genes involved in cytokine-receptor signaling including CISH, PIM1 and SOCS2, previously shown to be regulated by JAK2 pathway inhibition. 29,41 In addition to these changes, we also unexpectedly found STAT1 protein and transcript levels as well as its phosphorylation to be downregulated by JAK2 inhibition. Importantly, the regulation of STAT1 and the associated gene products was correlated highly with JAK2 on-target pharmacology and was shared across multiple inhibitors.…”
Section: Discussionmentioning
confidence: 84%
“…Consequently, caspase 3/7 activation and an associated increase in PARP and Mcl-1 cleavage occurred upon cotreatment with ruxolitinib and navatoclax. Aspects of these results have been noted in other disorders (13,20,21,36). Gozgit et al reported that inhibition of JAK2 blocked production of the Pim1/2 kinases and resulted in a corresponding decrease in BAD phosphorylation (13), and Will et al demonstrated that apoptosis induced by JAK2 inhibition is mediated by Bim and enhanced by the BH3 mimetic ABT-737 in JAK2 mutant human erythroid cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that activation of the JAK/ STAT pathway up-regulates the expression of antiapoptotic Bcl-2 family proteins and that inhibition of this pathway induces expression of proapoptotic BH3-only proteins, thereby inducing apoptosis (13,20,21). Treatment with ruxolitinib or IL-2 withdrawal reduced expression of p-STAT5 in all IL-2-dependent ATL cell lines (SI Appendix, Fig.…”
Section: Matrix Screening Highlights Ruxolitinib Drug Combinations Thatmentioning
confidence: 99%
See 1 more Smart Citation